2021
DOI: 10.1186/s13148-021-01043-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics integration identifies key upstream regulators of pathomechanisms in hypertrophic cardiomyopathy due to truncating MYBPC3 mutations

Abstract: Background Hypertrophic cardiomyopathy (HCM) is the most common genetic disease of the cardiac muscle, frequently caused by mutations in MYBPC3. However, little is known about the upstream pathways and key regulators causing the disease. Therefore, we employed a multi-omics approach to study the pathomechanisms underlying HCM comparing patient hearts harboring MYBPC3 mutations to control hearts. Results Using H3K27ac ChIP-seq and RNA-seq we obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 64 publications
5
26
0
1
Order By: Relevance
“…Lumican modulates collagen assembly and is implicated in tissue fibrosis via TGF-β interaction [52]. In a similar experiment, Pei et al applied proteomics, chromatin sequencing, and RNA sequencing to HCM and control tissue [53]. As with Coats et al, they found decreased enrichment of fatty acid metabolism via their proteomic data, which was corroborated by decreased RNA expression and hypoacetylation of key genes.…”
Section: Primary Human Tissuementioning
confidence: 89%
See 1 more Smart Citation
“…Lumican modulates collagen assembly and is implicated in tissue fibrosis via TGF-β interaction [52]. In a similar experiment, Pei et al applied proteomics, chromatin sequencing, and RNA sequencing to HCM and control tissue [53]. As with Coats et al, they found decreased enrichment of fatty acid metabolism via their proteomic data, which was corroborated by decreased RNA expression and hypoacetylation of key genes.…”
Section: Primary Human Tissuementioning
confidence: 89%
“…First, there are robust experimental methods for extracting metabolites and protein/phosphoproteins from specimens simultaneously with minimal losses. For example, liquid-liquid extraction (LLE) procedures can be used to selectively separate metabolites and proteins by differences in solubility, with subsequent solid-phase microextraction (SPME) allowing for purification of metabolites with minimal matrix interferences that confound LC/MS [53].…”
Section: "Emerging Integrative Omics: Spotlight On Metabolomics"mentioning
confidence: 99%
“…Among the GSA-enriched KEGG metabolic pathways between cardiomyopathy and normal samples, glycolysis/gluconeogenesis, oxidative phosphorylation, nucleotides metabolism, amino acid biosynthesis, co-factor metabolism, and fatty acid precursor arachidonic acid metabolism were statistically significant. Previous studies have reported oxidative phosphorylation, glycolysis and fatty acid metabolism perturbation in individual cardiomyopathies (23,24). In this work, we carried out an integrated analysis of AA metabolic perturbation across cardiomyopathies.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported a metabolic shift in energy sources during disease progression. HCM-focused transcriptome analysis showed down-regulated fatty acid metabolism (23). Similarly, in a DCM transcriptome analysis, mitochondrial dysfunction and oxidative phosphorylation pathways were significantly perturbed (24).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of common genetic variation at one or more of these loci may explain the variable disease expression observed in carriers of pathogenic sarcomeric variants 55 . Epigenetic factors may also influence HCM phenotype development by acting on signalling cascades, membrane receptors and transcription factors, or through proteomic upstream regulators of disease pathomechanisms, post-translational gene expression regulators and histone modification [56][57][58] .…”
Section: Clinical Features Of Paediatric Mybpc3 Variant Carriersmentioning
confidence: 99%